Seismic Evidence for Tectonically Dominated Seafloor Spreading in the Southwest Sub‐basin of the South China Sea - Junhui Yu; Pin Yan; Yanlin Wang; Jinchang Zhang; Yan Qiu; Manuel Pubellier; Matthias Delescluse (Geochemistry, Geophysics, Geosystems)
Abstract Seafloor spreading can be explained by different dynamic mechanisms, magmatically or tectonically dominated. The Southwest Sub‐basin, located at the southwest tip of the propagating seafloor spreading of the South China Sea, remains unclear for its spreading regime owing to poor and debated knowledge of the crustal structures. Here two multichannel seismic lines and one oceanic bottom seismometer line across this subbasin are reprocessed and analyzed with focus on crustal imaging. The sediments are usually 0.5–1.0 km thick over the abyssal basin and slightly thicker in the few grabens. The thickest (3.3 km) sediments are found in the fossil spreading center. The basement is fairly rough and highly faulted by ubiquitous crustal faults. The fossil spreading center is characterized by a deep median valley, similar to that of magma‐poor spreading cases. Both multichannel seismic lines show a few intermittent and diffusive reflectors at 1.5‐ to 3.6‐km depth below the fragmented basement. These reflectors, correlating well with the velocities of 6.8–7.2 km/s obtained from velocity inversion of oceanic bottom seismometer data, are interpreted as Moho reflections. Thus, the inferred crustal thickness is only 1.5–3.6 km excluding the sediments, which is much thinner than usual. The underlying mantle with velocities lower than 8.0 km/s might be serpentinized with water infiltration along these crustal faults. Therefore, it is proposed that the spreading of the Southwest Sub‐basin was tectonically dominated.